Antibacterial activity of Thymoquinone, an active principle of Nigella sativa and its potency to prevent bacterial biofilm formation - Bakhrouf Amina; Mahdouani Kacem; Jrah Hanene; Kouidhi Bochra; Chaieb Kamel (BMC, 2011)
Abstract Background Thymoquinone is an active principle of Nigella sativa seed known as "Habbah Al-Sauda" in Arabic countries and "Sinouj" in Tunisia. Bacterial biofilms tend to exhibit significant tolerance to antimicrobials drugs during infections. Methods The antibacterial activity of Thymoquinone (TQ) and its biofilm inhibition potencies were investigated on 11 human pathogenic bacteria. The growth and development of the biofilm were assessed using the crystal violet (CV) and the 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) reduction assay. Results TQ exhibited a significant bactericidal activity against the majority of the tested bacteria (MICs values ranged from 8 to 32 μg/ml) especially Gram positive cocci (Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis CIP 106510). Crystal violet assay demonstrated that the minimum biofilm inhibition concentration (BIC50) was reached with 22 and 60 μg/ml for Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis CIP 106510 respectively. In addition our data revealed that cells oxidative activity was influenced by TQ supplementation. In the same way, TQ prevented cell adhesion to glass slides surface. Conclusion The ability of TQ to prevent biofilm formation warrants further investigation to explore its use as bioactive substances with antibiofilm potential.